Moderate Islam and the Social Construction of Multi-Ethnic Communities in the hinterland of West Kalimantan - Zaenuddin Hudi Prasojo; Elmansyah Elmansyah; Muhammed Sahrin Haji Masri (Indonesian Journal of Islam and Muslim Societies, 2019)
This article discusses the social construction of culture and inter-ethnic relations within the daily lives of the people of West Kalimantan. Religion and ethnicity have played central roles in the identity dynamics of its multi-ethnic communities; they have also contributed to communal conflicts, with religious and cultural sentiments common throughout the region. Islam has become an important religion in West Kalimantan, as it is practiced by more than half of the province's population. This article explores the local potential of communities and the opportunity to promote better Islamic development in the region's hinterland after the collapse of the Islamic sultanates that had introduced Islam into this region. Data were obtained from ten different locations in Mempawah, Landak, and Sanggau Regencies, all of which are considered part of West Kalimantan's hinterland and are relatively homogenous in their demographics, religions, and customs. Over two years of research, we noted important local potentials and wisdoms in the region, finding that these complemented Islam within local communities' everyday lives. These local potentials and wisdoms included beliefsthat serving food strengthens brotherhood, friendliness is a key to success, lineage is a gift that should be appreciated, and serving guests brings happiness, as well as an ethos that promotes hard work and good manners.